An Atlas of Planar and Spect Bone Scans - Fogelman, Ignac. (Mosby, 1989)
This atlas considers in datail adult bone scanning with, Tc-labelled diphosphonates, and includes a limited selection of isms of tracer uptake and techniques for both planar and spect bone scanning are first described.